Robert B. Parker's Big shot [large type] - Parker, Robert B., 1932-2010; Farnsworth, Christopher (Parker, Robert B., 1932-2010. Jesse Stone novels., 2026)
"Ramsey Devlin doesn't think the law applies to him. This becomes apparent when Jesse finds him passed out, drunk, and on the side of the road in a McLaren worth more than most people's homes. After Devlin takes a swing at him and Jesse swiftly dumps him in the drunk tank, Jesse realizes he's made an enemy. Devlin Makes it his life's mission to use his money and influence to provoke Jesse. But when Devlin vanishes, and bloodstains are found on the carpet of his seaside mansion, Jesse must solve the case and prove his own innocence--or he might be the one to wind up behind bars"--